Racial Disparity Between Asian and Caucasian Crouzon Syndrome in Skull Morphology. Issue 8 (November 2020) - Lu, Xiaona; Forte, Antonio Jorge; Fan, Fei; Zhang, Zhiyong; Teng, Li; Yang, Bin; Alperovich, Michael; Steinbacher, Derek M.; Alonso, Nivaldo; Persing, John A.
Abstract : Background: Racial disparity in pathological consequences in skull growth may impact the treatment plan for different patient populations. This study attempts to explore the differences between Asian and Caucasian cranial morphology in Crouzon syndrome. Method: Ninety-one computed tomographic scans were included (Asian Crouzon syndrome, n = 12; Asian controls, n = 22; Caucasian Crouzon syndrome, n = 16; Caucasian controls, n = 41), and measured using Mimics and 3-matics software. Results: The entire cranial base length was reduced 11.92 mm ( P  = 0.004) in Asian Crouzon patients, and 14.58 mm ( P  < 0.001) in Caucasian Crouzon patients, compared to respective controls. The cranial base angle on the facial side of basicranium was more narrowed in Crouzon syndrome in both races, with similar changes of degrees (9.61°, P  = 0.002, in Asian Crouzon; 9.20°, P  = 0.019, in Caucasian Crouzon). However, the intracranial side was statistically more narrowed only in the Asian group (9.86°, P  = 0.003). Both Asian and Caucasian Crouzon patients developed reduced posterior fossa volume, by 15% ( P  = 0.034) and 17% ( P  = 0.004), respectively. However, Caucasian Crouzon patients developed a more shortened anterior and middle cranial base, than that of Asian patients. The separation of lateral pterygoids was only significantly increased in Caucasian patients (5.49°, P  < 0.001). Conclusion: Crouzon syndrome causes a shortened, widened, and kyphotic cranial base across both races. It also restricts the development of the posterior cranial fossa. However, the skull malformation is not the same between populations: Asian Crouzon patients developed more narrowed cranial base angulation on the intracranial side of basicranium, while Caucasian Crouzon patients developed more widened lateral pterygoids. Abstract : Supplemental Digital Content is available in the text